Application of Simultaneous 18F‐FDG PET With Monoexponential, Biexponential, and Stretched Exponential Model‐Based Diffusion‐Weighted MR Imaging in Assessing the Proliferation Status of Lung Adenocarcinoma. Issue 1 (10th December 2021) - Huang, Zhun; Li, Xiaochen; Wang, Zhixue; Meng, Nan; Fu, Fangfang; Han, Hui; Li, Dujuan; Bai, Yan; Wei, Wei; Fang, Ting; Feng, Pengyang; Yuan, Jianmin; et al.
Abstract : Background: Ki‐67 proliferation index (PI) is important for providing information on tumor behavior, treatment response, and prognosis. Integrated positron emission tomography/magnetic resonance (PET/MR) may have the potential to assess Ki‐67 PI in patients with lung adenocarcinoma. Purpose: To explore the value of simultaneous 18 F‐fluorodeoxyglucose ( 18 F‐FDG) PET/MR‐derived parameters in assessing the proliferation status of lung adenocarcinoma and to determine the best combination of parameters. Study Type: Prospective. Population: Seventy‐eight patients with lung adenocarcinoma and with Ki‐67 PI. Field Strength/Sequence: 3.0 T, simultaneous PET/MRI including diffusion‐weighted imaging (DWI) and 18 F‐FDG PET. Assessment: DWI‐derived parameters, namely, apparent diffusion coefficient (ADC), true diffusion coefficient ( D ), pseudo diffusion coefficient ( D *), perfusion fraction ( f ), diffusion heterogeneity index ( α ), and distributed diffusion coefficient (DDC); and PET‐derived parameters, namely, maximum standardized uptake value (SUVmax ), metabolic tumor volume (MTV), and total lesion glycolytic volume (TLG), were calculated and compared between the high (>25%) and low (≤25%) Ki‐67 PI groups. The correlations between PET‐derived parameters and DWI‐derived parameters were analyzed. Statistical Tests: Student's t ‐test, Mann–Whitney U test, chi‐square test, and receiver operating characteristic (ROC) curves. A P ‐value <0.05 was considered statistically significant. Results: The SUVmax, MTV, TLG, ADC, D, and DDC values were significantly different between the high ( N  = 35) and low Ki‐67 PI groups ( N  = 43). D, SUVmax, and MTV independently predicted the Ki‐67 PI status. The combination of D, SUVmax, and MTV had the largest area under the ROC curve (AUC = 0.900), which was significantly larger than the AUC alone of DDC (AUC = 0.725), SUVmax (AUC = 0.815), MTV (AUC = 0.774), or TLG (AUC = 0.783). The perfusion fraction did not correlate with SUVmax, MTV, or TLG ( r  = −0.03, −0.11, and −0.04, respectively; P  = 0.786, 0.348, and 0.733). Data Conclusion: The combination of D, SUVmax, and MTV may predict Ki‐67 PI status. No correlation was observed between perfusion parameters and metabolic parameters. Level of Evidence: 1 Technical Efficacy: Stage 2